Development of Argumentation Skills Assessment Instruments on Buffer Solution Material - Fitria Rahmatul Ula; Suyono (Postgraduate, University of Mataram, 2023)
This research aims to produce a qualified argumentation skill assessment according the criteria of validity and reliability. This research is a development research with the ADDIE model whose implementation is limited to the pilot implementation and the evaluation formative evaluation. The subject of this research was an argumentation skills assesment in buffer solutions implemented in 18 students grade XI of SMA Trensains Tebuireng. The research instruments are review sheets, validation sheets, and argumentation skill test sheets. The results of content validity gain a mode with scores of 4 and 5 with valid and very valid criteria. In the construct aspect, gain a mode with a score of 5 with very valid criteria. The empirical validity result of the five questions in order is 0.791; 0.876; 0.961; 0.927; and 0.871. The calculated value appropriate with the criteria of rcalculate > rtable so that it can be declared valid. The value of reliability obtained 0.922 is greater than the rtable which is 0.468. With such results, the instrument can be declared reliable. Based on the results of the analysis, the argumentation skill assessment instrument is qualified to be used to measure students' argumentation skills on buffer solution material.